The Development of Reading Comprehension Material Based on Vocabulary Collection Strategy at SMAN 13 Medan in Academic Year 2022/2023 - Lubis, Affan; Risnawaty (PT Inovasi Pratama Internasional, 2024)
The objective of this research is to develop the reading comprehension materials for Senior High School students based on Vocabulary Self-Collection Strategy at SMAN 13 Medan. The data of this research are quantitative and qualitative. The researcher uses the percentage of the questionnaire of need analysis for the quantitative data. Meanwhile, for the qualitative, the researcher uses the content analysis for describing the data. The data is collected by using questionnaire. The result of needs analysis showed two parts, those were target needs and learning needs. After gathering the need analysis.The researcher implemented ADDIE model for developing the materials. In order to maintain the students’ needs, the researcher created the theoretical model which consists of two big components namely; the components of reading comprehension and vocabulary self-collection strategy. The researcher develop the theoretical model which has been verified by the expert. The researcher finds that the model can give the big advantages to the students’ reading skills development.